Functional and transcriptomic insights into pathogenesis of R9C phospholamban mutation using human induced pluripotent stem cell-derived cardiomyocytes. (June 2018) - Ceholski, Delaine K.; Turnbull, Irene C.; Kong, Chi-Wing; Koplev, Simon; Mayourian, Joshua; Gorski, Przemek A.; Stillitano, Francesca; Skodras, Angelos A.; Nonnenmacher, Mathieu; Cohen, Ninette; Björkegren, Johan L.M.; Stroik, Daniel R.; et al.
Abstract: Dilated cardiomyopathy (DCM) can be caused by mutations in the cardiac protein phospholamban (PLN). We used CRISPR/Cas9 to insert the R9C PLN mutation at its endogenous locus into a human induced pluripotent stem cell (hiPSC) line from an individual with no cardiovascular disease. R9C PLN hiPSC-CMs display a blunted β-agonist response and defective calcium handling. In 3D human engineered cardiac tissues (hECTs), a blunted lusitropic response to β-adrenergic stimulation was observed with R9C PLN. hiPSC-CMs harboring the R9C PLN mutation showed activation of a hypertrophic phenotype, as evidenced by expression of hypertrophic markers and increased cell size and capacitance of cardiomyocytes. RNA-seq suggests that R9C PLN results in an altered metabolic state and profibrotic signaling, which was confirmed by gene expression analysis and picrosirius staining of R9C PLN hECTs. The expression of several miRNAs involved in fibrosis, hypertrophy, and cardiac metabolism were also perturbed in R9C PLN hiPSC-CMs. This study contributes to better understanding of the pathogenic mechanisms of the hereditary R9C PLN mutation in the context of human cardiomyocytes. Highlights: Dilated cardiomyopathy can be caused by hereditary mutations in phospholamban (PLN). hiPSC lines can be generated with PLN mutations using CRISPR/Cas9. R9C PLN causes a blunted β-agonist response and abnormal calcium handling. R9C PLN results in activation of hypertrophy and increased cardiomyocyte size. RNA-seq suggests altered metabolic state and profibrotic signaling in R9C hiPSC-CMs.